Imperial Russia : new histories for the Empire - Burbank, Jane; Ransel, David L. (Indiana-Michigan series in Russian and East European studies., 1998)
"On the basis of the work presented here, one can say that the future of American scholarship on imperial Russia is in good hands."--American Historial Review" ... innovative and substantive research ..."--The Russian Review"Anyone wishing to understand the 'state of the field' in Imperial Russian history would do well to start with this collection."--Theodore W. Weeks, H-Net Reviews"The essays are impressive in terms of research conceptualization, and analysis."--Slavic ReviewPresen